The organisational performance impact of ERP systems on selected manufacturing companies within South Africa - Hart, Colin Anthony (My University, 2011)
Preliminary investigation indicated that there is a need to determine the performance benefits that South African manufacturing firms are gaining from Enterprise Resource Planning (ERP) systems. Clarification on the factors contributing to ERP success is also required. Consequently the central research problem is: To determine the impact of ERP systems on organisational performance, by analysing achieved ERP benefits within the framework of a suitable Performance Measurement System (PMS), and to investigate an association between Critical Success Factors (CSF) and ERP benefits. By conducting a literature review a list of expected ERP benefits and CSFs is compiled. PMSs are evaluated and an appropriate model is designed for the purpose of ERP impact evaluation. The identified ERP benefits and CSFs are refined by means of a series of structured interview sessions with local ERP experts. The results of the interview sessions are built into a questionnaire, which is used in a survey within the South African manufacturing sector. The results of the study indicate that business benefits are being realised by manufacturing companies who have implemented ERP systems. By building these benefits into the chosen performance measurement model it is shown that these benefits have a positive impact on organisational performance. Although a core list of CSFs is identified, and three associations are proposed between CSFs and ERP benefits, further research is suggested to validate these findings.